The Value of C-Arm Computed Tomography in Addition to Conventional Digital Subtraction Angiography in the Diagnostic Work-up of Patients with Suspected Chronic Thromboembolic Pulmonary Hypertension: An Update of 300 Patients - Maschke, Sabine K; Werncke, Thomas; Becker, Lena S; Dewald, Cornelia L A; Meine, Timo C; Olsson, Karen M; Fuge, Jan; Hoeper, Marius M; Wacker, Frank K; Meyer, Bernhard C; Hinrichs, Jan B (Academic radiology, 2022)
To assess the value and possible benefit of combined C-arm computed tomography (CACT) and conventional digital subtraction angiography (DSA) of the pulmonary arteries in the diagnostic work-up of patients with suspected chronic thromboembolic pulmonary hypertension (CTEPH). We evaluated 308 pulmonary artery angiographies of 308 consecutive patients with suspected CTEPH. Seven patients were excluded because of incomplete imaging. Thus, 301 datasets were included in our study. The pulmonary artery segments and their subsegmental branching were independently evaluated by two readers (R1, R2) using both, DSA and CACT for optimal image quality. Subsequently, the diagnostic findings were compared. Inter-modality and inter-observer agreement were calculated. Consensus reading was done and correlated to a standard of reference, representing the overall consensus of both modalities. Fisher's exact test and Cohen's Kappa were applied. A total of 5719 pulmonary segments were evaluated of which only 28 segments (0.4%) were rated to be nondiagnostic on both, CACT and DSA. Overall, 5640 (98.6%) and 5600 (97.9%) pulmonary segments were rated to be diagnostic in DSA and CACT, respectively. The main causes of nondiagnostic image quality were motion artifacts on both, CACT (R1:81, R2:50) and DSA (R1:60, R2:48). Interobserver agreement was excellent for DSA (κ = 0.9) and CACT (κ = 0.91) and intermodality agreement was substantial (R1: κ = 0.69, R2: κ = 0.77). Compared to standard of reference, the intermodality agreement for CACT was excellent (κ = 0.96), whereas it was inferior for DSA (κ = 0.75), due to the higher number of pathologic findings in CACT read as normal on DSA. CACT of the pulmonary arteries can provide additional information to DSA during CTEPH work-up. Moreover, the combination of CACT and DSA can minimize the portion of non-diagnostic examinations, therefore being a reasonable combination to optimize the diagnostic work-up.